Implementing a cirrhosis order set in a tertiary healthcare system: a theory-informed formative evaluation - A. M. Hyde; E. Johnson; T. Luig; D. Schroeder; M. Carbonneau; D. Campbell-Scherer; P. Tandon (BMC, 2023)
Abstract Background Standardized order sets are a means of increasing adherence to clinical practice guidelines and improving the quality of patient care. Implementation of novel quality improvement initiatives like order sets can be challenging. Before the COVID-19 pandemic, we conducted a formative evaluation to understand healthcare providers' perspectives on implementing clinical changes and the individual, collective and organizational contextual factors that might impact implementation at eight hospital sites in Alberta, Canada. Methods We utilized concepts from the Consolidated Framework for Implementation Research (CFIR) and Normalisation Process Theory (NPT) to understand the context, past implementation experiences, and perceptions of the cirrhosis order set. Eight focus groups were held with healthcare professionals caring for patients with cirrhosis. Data were coded deductively using relevant constructs of NPT and CFIR. A total of 54 healthcare professionals, including physicians, nurses, nurse practitioners, social workers and pharmacists and a physiotherapist, participated in the focus groups. Results Key findings revealed that participants recognized the value of the cirrhosis order set and its potential to improve the quality of care. Participants highlighted potential implementation challenges, including multiple competing quality improvement initiatives, feelings of burnout, lack of communication between healthcare provider groups, and a lack of dedicated resources to support implementation. Conclusions Implementing a complex improvement initiative across clinician groups and acute care sites presents challenges. This work yielded insights into the significant influence of past implementation of similar interventions and highlighted the importance of communication between clinician groups and resources to support implementation. However, by using multiple theoretical lenses to illuminate what and how contextual and social processes will influence uptake, we can better anticipate challenges during the implementation process.